From Wellbeing to Social Media and Back: A Multi-Method Approach to Assessing the Bi-Directional Relationship Between Wellbeing and Social Media Use - Griffioen, Nastasia; Lichtwarck-Aschoff, Anna; van Rooij, Marieke; Granic, Isabela (Frontiers in Psychology, 2021)
Literature concerning the relationship between social media use and wellbeing is inconsistent in its findings, and most research has focused on time spent on social media rather than on what emerging adults do there, with whom, and why. Here, we investigated whether momentary social stress affects emerging adults’ social media use, and whether this social media use relates to subsequent changes in wellbeing. We implemented a multi-method paradigm utilising objective and self-report data to investigate how social stress relates to how (much) and why emerging adults use social media. We report on findings based on 114 17-25-year-old emerging adults recruited on university campus. Our findings suggest that social stress does not affect adolescents’ subsequent social media use, and that there is no relationship between social media use after stress and changes in momentary wellbeing. Our work illustrates the need for detailed approaches in social media and psychological wellbeing research.